2021
DOI: 10.21203/rs.3.rs-802409/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hijacking of transcriptional condensates by endogenous retroviruses

Abstract: Endogenous retroviruses (ERVs) comprise ~10% of mammalian genomes, and ERVs are repressed by multiple cellular mechanisms including heterochromatin, DNA methylation, and methylation of their RNA transcripts 1-13. Although the vast majority of ERVs in mammals are incapable of retrotransposition, ERV de-repression during early development is associated with embryonic lethality 14-16, suggesting that ERV transcription or RNA transcripts may underlie essentiality of ERV repression. Here we report that rapid and se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…We therefore tested whether the frameshift mutation alters the partitioning of HMGB1 into nuclear condensates. Using purified marker proteins, we assembled the following model condensates: recombinant mCherry-tagged MED1 IDR droplets as an in vitro model for Mediator co-activator condensates 29,31,33 ; mCherry-tagged HP1α droplets as an in vitro model for heterochromatin 34 ; and mCherry-tagged NPM1 droplets as an in vitro model for the granular component of the nucleolus 35 . Wild-type and…”
Section: Altered Hmgb1 Phase Separation In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore tested whether the frameshift mutation alters the partitioning of HMGB1 into nuclear condensates. Using purified marker proteins, we assembled the following model condensates: recombinant mCherry-tagged MED1 IDR droplets as an in vitro model for Mediator co-activator condensates 29,31,33 ; mCherry-tagged HP1α droplets as an in vitro model for heterochromatin 34 ; and mCherry-tagged NPM1 droplets as an in vitro model for the granular component of the nucleolus 35 . Wild-type and…”
Section: Altered Hmgb1 Phase Separation In Vitromentioning
confidence: 99%
“…Protein expression of mCherry constructs was performed as previously described 6,33 , but with modifications to mCherry-MED1-IDR expression, which was performed in the presence of 400 µg ml -1 kanamycin. Protein expression of meGFP-HMGB1 constructs was performed in Rosetta (DE3)pLysS cells (Sigma-Aldrich) in the presence of 25 µg ml -1 chloramphenicol and 100 µg ml -1 ampicillin.…”
Section: Protein Purification and Peptide Synthesismentioning
confidence: 99%
“…RNA molecules are pervasive components of active transcriptional regulatory loci (Asimi et al, 2022; Henninger et al, 2021; Kaikkonen and Adelman, 2018; Seila et al, 2008; Sharp et al, 2022) and have been implicated in the formation and regulation of spatial compartments (Quinodoz et al, 2021). The noncoding RNAs produced from enhancers and promoters are known to affect gene expression (Kaikkonen and Adelman, 2018), and plausible mechanisms by which these RNA species could influence gene regulation have been proposed to include binding to cofactors and chromatin regulators (Bose et al, 2017; Lai et al, 2013; Long et al, 2017), and electrostatic regulation of condensate compartments (Henninger et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although several HERV subfamilies are expressed in a tight spatiotemporal mode in early human embryos, HERV expression is largely repressed in early human embryos, and its derepression is associated with lethality at various embryonic stages [30,76]. It has been reported that ERV derepression triggered upon acute perturbation of the repression machinery generates ERV RNAs at hundreds or maybe even thousands of genomic loci, disrupting phase-separated transcriptional condensates enriched in RNA polymerase II in the nucleus [12].…”
Section: Germ Cells and Early Embryosmentioning
confidence: 99%
“…The DNA modification. Nevertheless, some distinct HERVs are competent to produce transcripts or proteins, which participate in crucial processes such as transcription in the nucleus, immune system activation, and placenta development [11][12][13].…”
Section: Introductionmentioning
confidence: 99%